(untitled) (CIPEEX, 2025)
Beach Handball is an emerging sport that has gained popularity due to its unique characteristics and the physical demands it imposes on athletes. The modality in question is played on sand, which significantly influences the physiological and mechanical aspects of the game. The physical fitness of beach handball players encompasses several components, including strength, endurance, and powers. In this sense, handgrip strength is crucial in the specific execution, such as throwing and catching the ball. In this study, we verified the characteristics of athletes and the muscle strength of athletes from different positions. A total of 36 athletes of both sexes aged 18 to 21 years were evaluated. They are using a hydraulic dynamometer (SH 5001, Saehen, Korea) to measure handgrip strength. The normality of the data was tested (Kolmogorov Smirlov), and the level of significance adopted was plt;0.05. The mean age, body mass, and height were 19.61±0.99 years, 66.15±15.79 kg, 167.61±8.80 cm, respectively. Regarding strength, beach handball athletes presented acceptable levels with their adult peers. Its strength score was 29.38±8.92 kgf. Therefore, this study presented an initial contribution to establish the strength profile of the athletes of the modality under study, being relevant for references of normality of strength of the beach handball athletes of the institution but future research is needed related to the strength of adults since the measurements performed are preliminary and specific to the aforementioned modality.